Religious Moderation Education in the Relationship between Islamic Boarding Schools and the Chinese Ethnicity in the Chinatown of Rembang City - Husna Nashihin; Edi Purnama; Triana Hermawati (At Turots: Jurnal Pendidikan Islam, 2023)
In a socio-cultural context, 94% of the population in Lasem is of Chinese ethnic descent, and 4% are of native descent, which is why Lasem is better known as "kota pecinan" or the Chinatown city. The relationship between Pondok Pesantren Kauman and the Chinese ethnic community in Chinatown is a rare and unique phenomenon rich in values of moderate religious education, making it important to be studied. This qualitative descriptive research utilizes a phenomenological approach to examine the practice of religious moderation in the relationship between Pondok Pesantren Kauman and the Chinese ethnic community. Data collection is carried out through observation, documentation, and interviews with 5 elder kyai, 6 officials, 21 educators, 12 ustadz (Islamic scholars), and 30 santri (students). This research has three objectives: to analyze the relationship, practices, and values of religious moderation education in Pondok Pesantren Kauman and the Chinese ethnic community. The research reveals that the relationship of religious moderation between Pondok Pesantren Kauman and the Chinese ethnic community can be categorized into two dimensions: theological and sociological. The practice of religious moderation is physically reflected in the acculturation of Javanese-Arabic-Chinese architectural elements, as well as non-physical aspects in their commitment to instilling the values of Islam Rahmatan lil 'Alamin (a blessing to all worlds). There are 29 values of religious moderation education in the relationship between Pondok Pesantren Kauman and the Chinese ethnic community that relate to the characteristics of Islam Rahmatan lil 'Alamin, which include values such as tawasuth (moderation), infitah (inclusivity), tawazun (balance), and musawah (equality).